HUBUNGAN KOMITMEN DAN MOTIVASI DENGAN KINERJA TENAGA PENDIDIK DI SEKOLAH POLISI NEGARA POLDA SUMBAR - Hendri Mispar (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
Background of this research is the low achievement of instructors’ performance of National Police School of West Sumatera Police Headquarter. The purpose of this research is to know the significance of correlation between instructors’ performance of National Police School of West Sumatera Police Headquarter.  This research is a descriptive research by using correlational method. Ex post facto. The hyphothesis of this research were: (1) is there any correlation between commitment toward instructors’ performance of National Police School of West Sumatera Police Headquarter. (2) ) is there any correlation between motivation toward instructors’ performance of National Police School of West Sumatera Police Headquarter.  (3)  is there any correlation between commitment and motivation  toward instructors’ performance of National Police School of West Sumatera Police Headquarter.Population of this research were all of the instructors of National Police School (SPN) of West Sumatera Police Headquarter, they were 80 instructors.  Samples of this research were 60 person of the instructors.  Samples were taken by uing Slovin method. The data were analyzed by using Statistical Program for Social Studies (SPSS) 20 version. Based on the data analysis of this research, it can be concluded that: (1) the commitment of the instructors has a positive and significant correlation toward instructors’ performance of National Police School of West Sumatera Police Headquarter.  (2) the motivation of the instructors has no positive and no significant correlation toward instructors’ performance of National Police School of West Sumatera Police Headquarter.  (3) both commitment (X1) and motivation (X2) have positive correlation toward performance (Y) of the instructors’ of National Police School of West Sumatera Police Headquarter.